Main Factors of Mesozoic Tectonic Deformation in the Erlian Basin, Inner Mongolia, China: Insights from Physical Modelling. (4th May 2022) - Zhao, Yue; Xu, Qiang; Li, Yongchen; Bai, Xiujia; Ding, Rong; Wang, Jianxin; Hou, Tao
Abstract : Erlian Basin is a Mesozoic oil and gas-bearing basin in northeast of China. The extension rate, extension direction, and stratum thickness of this rift basin have a clear control on its shape and extension. In this study, we design three sandbox models of the Erlian Basin to represent the effects of changing these three factors. The extension rate controls the timing of secondary fault formation inside the rift basin; a high extension rate promotes faster deformation inside the rift. The extension direction controls the strike of the fault inside the rift; a greater angle between the extension direction and the normal direction of the strike of the rift favors rapid evolution of internal secondary faults. The stratum thickness represents the control of sedimentation on the rift basin; the thinner the brittle layer, the wider the rift. The simulation results also show that the extension direction is the major factor controlling tectonic deformation in the basin. Stratum thickness and extension rate are secondary controlling factors. Additionally, according to geometric and kinematic similarities between typical Mesozoic rift basins in eastern and adjacent areas of China, we suggest that southeastward extension is a possible kinematic mechanism for basin formation.